Impacts of protein–protein interaction domains on organism and network complexity - Xia, Kai; Fu, Zheng; Hou, Lei; Han, Jing-Dong J.

(untitled) (Genome Research, 2008)
It has been a puzzle that genome or proteome sizes are not correlated with the complexity of the organisms. Although alternative splicing and noncoding and regulatory elements explain some of the differences, the complexity of the protein interaction network and regulatory network may provide additional explanations. Here, we collected 642 domains that mediate protein–protein interactions (PPIs) and examined the evolution of the PPI domains and its impact on organismal complexity and PPI network complexity. In agreement with previous more general studies of protein domains, a significant expansion of PPI domains per proteome was found in metazoa. We also found both the number and coverage of PPI domains per protein increased. However, a better correlation with complexity was seen with increasing PPI domain coverage per protein, so that proteins in complex organisms are more compact and specialized in PPI. Such a structural adaptation of the proteins is correlated with the number of interactions that the proteins can make in PPI networks, and seems to be a more favorable way to increase network connectivity than other structural adaptations.